Consideraciones para calcular el ratio precio-utilidad de la bolsa de valores de Lima: metodología y aplicaciones - Pereda, Javier (2012)
In this paper we construct a methodology to calculate the price-earnings ratio (PER) of the General Index of the Lima Stock Exchange (IGBVL) for the period 1995-2011 following Shiller (2005). Results show that equity prices, in the analyzed period, basically responded to the expected evolution of earnings of the companies, even during the period of the equity prices boom that preceded the financial crisis of 2008. This conclusion is reinforced when we calculate, following Hayford y Malliaris (2004), the implicit equity premia expected for stock investors. We find high values of equity premia during the period of stock prices boom, which would justify the high PER values registered in that period